Potensi Daun Kersen (Muntingia calabura L.) sebagai Herbal Pendukung Pengelolaan Gula Darah: Tinjauan Literatur dan Implikasinya dalam Wellness Tourism - Ni Nyoman Anandia Vidya Paramita; Irma Rahmayani; Ni Made Widya Pradnya Dewani; Agastya Cahya Ariadi; Ida Bagus Gde Ari Janar Dana; I Ketut Tirta Buana (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Blood sugar regulation problems such as diabetes are increasing, so sustainable management is needed. Kersen leaves (Muntingia calabura L.) are tropical plants that have potential as traditional blood sugar management through the content of phytochemical compounds contained therein. This article aims to review the potential of kersen leaves in blood sugar management and its implications in the wellness tourism approach. The method used is a literature review of scientific literature, especially the last five years related to the phytochemical content and antihyperglycemic activity of kersen leaves, as well as their implications in wellness tourism. The results of the literature review through in vivo and in vivo approaches show that kersen leaves contain potential phytochemical compounds such as flavonoids, phenols, tannins, alkaloids, and saponins that are able to regulate blood sugar by preventing the oxidation process of important molecules by free radicals, suppressing oxidative stress, inhibiting carbohydrate enzymes, increasing insulin production, and suppressing the glycogenolysis process. In the context of wellness tourism, kersen leaves as a herbal plant can be used as a healthy drink and have the potential to be studied further in the development of wellness tourism, especially related to herbal medicine.